Teacher's Pedagogical Competence in Teaching English In Secondary School - Muhammad Nur Khamid; Tusino; Sri Widodo (Universitas Islam Negeri Palopo, 2026)
This research aimed to analyze the pedagogical competence of English teachers, focusing on lesson planning and classroom implementation. Although pedagogical competence is widely recognized as a key factor in effective English language teaching, limited studies have examined its implementation in Islamic junior high schools, particularly by integrating both teacher and student perspectives. This research employed a qualitative design involving two English teachers and 52 eighth-grade students at MTs Al-Iman Bulus. The data were collected through observation, semi-structured interviews, questionnaires, and documentation. They changed their teaching materials. Used different ways to engage students, like games, videos, and group tasks. Students liked these approaches: the friendly classroom environment, fair grading, and clear explanations. The students gave ratings with the classroom atmosphere (3.63), fair assessment (3.58), and clear explanations (3.56). However, teachers still faced challenges, like students having varying skill levels, not enough time, and some students lacking motivation. To overcome these, teachers used teaching methods that helped all students and activities that encouraged participation. Teachers adapted their teaching to meet the needs of all students and used activities. The results show that good teaching skills are really important for making classroom learning work and keeping students interested. Teachers need to keep trying to give feedback and use teaching tools in the right way. This research is helpful for English teachers at MTs Al-Iman Bulus and other similar Islamic junior high schools. It gives them ideas on how to make their teaching help students who are different and get students to take part in class. The results of this research can also help schools and educators come up with plans to make English language teaching and learning better.